1986
DOI: 10.1002/path.1711490108
|View full text |Cite
|
Sign up to set email alerts
|

Collagenous colitis: A disease of pericryptal fibroblast sheath?

Abstract: Mucosal biopsies from four women with collagenous colitis and ten controls were studied. By light microscopy the cells of the pericryptal fibroblast sheath appeared diminished in number but increased in size in collagenous colitis. Electron optically in the controls the pericryptal fibroblasts were in intimate contact with the epithelial basal lamina in the crypts. On the free surface the fibroblasts maintained contact with the epithelial cells by attenuated cell processes. In collagenous colitis, in the middl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(28 citation statements)
references
References 22 publications
1
26
0
1
Order By: Relevance
“…Collagenous colitis combined with coeliac disease and some degree of villous atrophy has been described in about ten patients [9,12,24,25,47,50]. However, the small number of patients with this combination is in marked contrast with over 200 reported cases of patients with collagenous colitis but without malabsorption and with biopsy-proven normal small gut.…”
Section: Coexisting Immune-related Diseasesmentioning
confidence: 92%
See 1 more Smart Citation
“…Collagenous colitis combined with coeliac disease and some degree of villous atrophy has been described in about ten patients [9,12,24,25,47,50]. However, the small number of patients with this combination is in marked contrast with over 200 reported cases of patients with collagenous colitis but without malabsorption and with biopsy-proven normal small gut.…”
Section: Coexisting Immune-related Diseasesmentioning
confidence: 92%
“…In 1986, the first three cases of collagenous colitis, coexisting with small intestinal villous atrophy [24,25] and the first autopsy case [49] were reported.…”
Section: The Years Of Progress and Controversy (1986-1993)mentioning
confidence: 99%
“…Ultrastructural studies have demonstrated exten sive changes of the pericryptal fibroblasts in collagenous colitis. The fibroblasts have been noted to take the features of myofibroblasts, the proliferative cells often seen in granula tion tissue [32]. However, this theory does not account for the lamina propria inflammation or the fact that the type of collagen deposited is the type found in any reparative process.…”
Section: Pathogenesismentioning
confidence: 96%
“…Еще в 80-х годах XX века высказано предположение, что КК связан с альтерацией синтеза коллагена. При проведении иммуно-гистохимического анализа установлено, что субэпителиальные слои состоят из коллагена I и III типов [49,50]. Тем не менее в по-следующем исследовании, проведенном T. Aigner и соавт.…”
Section: терапевтический архив 4 2015unclassified